2012
DOI: 10.1152/ajprenal.00643.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of renin activity slows down the progression of HIV-associated nephropathy

Abstract: In the present study, we evaluated the effect of inhibition of renin activity (aliskiren) on the progression of renal lesions in two different mouse models (Vpr and Tg26) of human immunodeficiency virus (HIV)-associated nephropathy (HIVAN). In protocol A, Vpr mice were fed either water (C-VprA) or doxycycline [Doxy (D-VprA)] in their drinking water for 6 wk. In protocols B and C, Vpr mice received either normal saline (C-VprB/C), Doxy + normal saline (D-VprB/C), or Doxy + aliskiren (AD-VprB/C) for 6 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It has been reported that Tg26 displays slightly elevated BP compared with wild-type littermates and that ARBs can reduce BP in Tg26 mice. 37,38 In summary, we used a computational approach to predict a drug combination based on a database of drug-induced gene expression signatures. This tool helped us to predict potential drug combinations after incorporating the differential gene expression profiles from the disease model of HIVAN.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Tg26 displays slightly elevated BP compared with wild-type littermates and that ARBs can reduce BP in Tg26 mice. 37,38 In summary, we used a computational approach to predict a drug combination based on a database of drug-induced gene expression signatures. This tool helped us to predict potential drug combinations after incorporating the differential gene expression profiles from the disease model of HIVAN.…”
Section: Discussionmentioning
confidence: 99%
“…Breeding pairs to develop Tg26 colonies were kindly gifted by Prof. Paul E. Klotman M.D., President and CEO, Baylor College of Medicine, Houston, TX. Details of these mice have been described previously (Kumar et al, 2010, 2011, 2012; Rai et al, 2013). We are maintaining the colonies of these animals in our animal facility.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of renin angiotensin system (RAS) has been demonstrated to play an important role in the development as well as progression of HIVAN (Kumar et al, 2011, 2012). Modalities which either blocked the production of Ang II or inhibited the effect of Ang II have been reported to slow down the progression of HIVAN (Bird et al, 1989; Burns et al, 1999; Kimmel et al, 2003); moreover, infusion of Ang II accelerated the progression of renal lesions in a mouse model of HIVAN (Ideura et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these factors are also present in patients with HIV-associated nephropathy (HIVAN) (6, 7); however, the role of epigenetic factors in the development of HIVAN has not been studied so far (8). The renin angiotensin system (RAS) has been shown to play important roles in the development and progression of HIVAN (9-13). For example, infusion of Ang II enhanced progression of HIVAN in an experimental mouse model of the disease (9).…”
mentioning
confidence: 99%
“…Conversely, blockade and inhibition of Ang II production slowed down HIVAN progression both in human and animal models (10-12). Similarly, enhanced renin production accelerated progression of renal lesions, whereas inhibition of renin attenuated progression of renal lesions in Vpr transgenic mice (an HIVAN model) (13). Recent reports indicate that lack of VDR in the genome of T cells is associated with the activation of the RAS (14).…”
mentioning
confidence: 99%